UUM ties up with CIMA - The Edge, Financial Daily (The Edge Financial Daily, 2011)
KUALA LUMPUR: University Utara Malaysia (UUM) accounting undergraduates will soon be able to simultaneously earn the Chartered Institute of Management Accounting CIMA professional accreditation with their degrees.